Implementation of Balanced Scorecard in Improving Private Universities’ Performance - Novi Ruhviyanti; Sepryhatin Dioputra; Achmad Pahrul Rodji (Ridwan Institute, 2023)
The role of private universities in improving quality must accommodate all aspects of the performance of the tri dharma of higher education. The rapid development of higher education institutions must be ready to change. Changes in the global business environment also trigger the increasing intensity of competition between higher education service providers so that each higher education service provider will try to offer high-performance higher education services. This research aims to see how far the implementation of BSC is in improving the performance of private universities. Specifically, this study describes four perspectives, including (1) financial perspective, (2) customer perspective, (3) internal business process perspective (4) learning and growth perspective. They were using the theory of Robert Kaplan and David Norton. This study uses a descriptive method with a qualitative approach and data collection by conducting observations, interviews, and documentation studies. The research results indicate that the BSC implementation has been applied in a systematic, measurable, and planned manner so that the Vision, Mission, and objectives are achieved. In an implementation, there is a balance between financial and non-financial.